2022
DOI: 10.1101/2022.03.31.486525
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pulmonary dust foci as rat pneumoconiosis lesion induced by titanium dioxide nanoparticles in 13-week inhalation study

Abstract: Background: Most toxicological studies on titanium dioxide (TiO2) particles to date have concentrated on carcinogenicity and acute toxicity, with few studies focusing of pneumoconiosis, which is a variety of airspace and interstitial lung diseases caused by particle-laden macrophages. The present study examined rat pulmonary lesions associated with pneumoconiosis after inhalation exposure to TiO2 nanoparticles (NPs). Methods: Male and female F344 rats were exposed to 6.3, 12.5, 25, or 50 mg/m3 anatase type TiO… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 65 publications
(94 reference statements)
2
3
0
Order By: Relevance
“…It has been reported that AEPs are present in mouse and human lungs to contribute to the activation of regenerative molecular programs [11,12] and that Sox9-positive AEPs also exist [19]. Although in this study, we were not able to identify AEPs in normal rat lungs, consistent with our previous findings in rats [13], AEPs were observed immediately after CWAAP-A exposure and after the 18-week recovery period, suggesting that CWAAP-A induced lung lesions are regenerative changes, consistent with previous reports [11]. Furthermore, a small number of Sox9-positive AEPs were also observed in the lesions after the 18-week recovery period.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…It has been reported that AEPs are present in mouse and human lungs to contribute to the activation of regenerative molecular programs [11,12] and that Sox9-positive AEPs also exist [19]. Although in this study, we were not able to identify AEPs in normal rat lungs, consistent with our previous findings in rats [13], AEPs were observed immediately after CWAAP-A exposure and after the 18-week recovery period, suggesting that CWAAP-A induced lung lesions are regenerative changes, consistent with previous reports [11]. Furthermore, a small number of Sox9-positive AEPs were also observed in the lesions after the 18-week recovery period.…”
Section: Discussionsupporting
confidence: 88%
“…9 right panels). These results are consistent with our previous report [13] and confirm that AEPs are conserved in the rat lung and may be involved in the formation and progression of CWAAP-A induced lung lesions. Furthermore, these results support the premise that AEP expansion in the lesion represents a regenerative change in the alveoli in response to alveolar toxicity caused by exposure to CWAAP-A.…”
Section: Alveolar Epithelial Progenitor Cells (Aeps) Are Conserved In...supporting
confidence: 94%
See 2 more Smart Citations
“…We have previously conducted systemic inhalation exposure studies of various chemicals in rodents, including rasH2 mice, and have examined various toxicities, including carcinogenicity and pulmonary fibrosis [25][26][27] . In this study, we conducted a 26-week systemic inhalation exposure study of 2-BP using rasH2 mice and comprehensively evaluated carcinogenicity in each organ and reproductive organ toxicity.…”
Section: Introductionmentioning
confidence: 99%